SIKAP MAHASISWA TERHADAP PELAKSANAAN PENDIDIKAN INKLUSI - Nirsantono Hasnul (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
The aim of this study is describe the implementation of inclusive education at the Department of Special Education, School of Education, State University of Jakarta. The research carried out in 2009 employed survey method. The data was collected using questionnaire by survey including 40 students as the samples out of the population of 70 regular students. The samples consisted of 35 students of 2006 academic year and 5 students of 2005 academic year. The conclusion of the research show that the students have positive attitude towards inclusive education.